2002
DOI: 10.1103/physrevb.65.054107
|View full text |Cite
|
Sign up to set email alerts
|

First-principles studies of the structural and electronic properties of pyriteFeS2

Abstract: We present a study of the structural and electronic properties of Pyrite FeS 2 performed using both localized basis set and plane wave first-principles calculations. Calculations performed using either Gaussian or plane wave basis sets yield results consistent with each other. Small differences in the computed geometries are shown to be due to the choice of pseudopotential employed in the plane wave calculations. The computed densities of states are relatively insensitive to the form of basis set and pseudopot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 61 publications
5
44
0
Order By: Relevance
“…Regular GGA-PBE calculations usually underestimate the lattice constant and band gap of pyrite crystals; some previous calculations even predicted a metallic rather than a semiconducting state for bulk pyrite. 42,43 More sophisticated schemes such as the hybridized exchange-correlation functional (HSE06) 44 or Hubbard U correction 45 are therefore needed for reliable studies of pyrite systems. In this work, we examined both HSE06 and GGA+U schemes and found that the latter, with U = 2 eV for Fe d-orbitals, is more appropriate for the correct description of electronic properties of bulk pyrite.…”
Section: Resultsmentioning
confidence: 99%
“…Regular GGA-PBE calculations usually underestimate the lattice constant and band gap of pyrite crystals; some previous calculations even predicted a metallic rather than a semiconducting state for bulk pyrite. 42,43 More sophisticated schemes such as the hybridized exchange-correlation functional (HSE06) 44 or Hubbard U correction 45 are therefore needed for reliable studies of pyrite systems. In this work, we examined both HSE06 and GGA+U schemes and found that the latter, with U = 2 eV for Fe d-orbitals, is more appropriate for the correct description of electronic properties of bulk pyrite.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of correlation effects in iron systems has also been highlighted in recent studies of FeS 2 where it was reported that the poor description of the structure and electronic properties of this material was due to the failure of HF theory to describe the low-spin Fe 2+ ion. 36 The inclusion of correlation effects, through DFT, hybrid functionals ͑B3LYP͒ or a posteriori correlation corrections resulted in much improved structural parameters.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has also been employed very successfully in the past to accurately describe the bulk, surface and electronic properties of numerous minerals. [16][17][18] Pyrite itself has received much attention from computational methods, including DFT [19][20][21] and interatomic potential based studies. 22 In contrast, theoretical studies involving the marcasite phase are very limited, with one study comparing the thermodynamics of arsenic incorporation into pyrite and marcasite.…”
Section: Methodsmentioning
confidence: 99%